The coining practical wisdom and the virtue of marriage (With Looking at the views of Ayatollah Javadi Amoli) - Hadi Mousavi (اخلاق وحیانی)
Marriage as an action that is the way to enter the family institution is discussed in Islamic thought under the knowledge of practical wisdom. What is the relationship between practical wisdom and marriage? The answer is a discussion of knowledge in Islamic wisdom under the title of coining practical wisdom; the purpose of this article is to deal with the relationship between practical wisdom and jurisprudence; Jurisprudence is a system of knowledge that forms various legal systems through marriage as a matter of stability for man and society. Therefore, it has been revealed in a rational method of ijtihad, on the one hand, that marriage as a moral virtue is meaningful within the practical wisdom, and on the other hand, this virtue makes possible the perfections of the individual human being and, on the other hand, the social perfections in the form of the four chains of Sharia. In fact, these two types of perfection actualize what is mentioned in Sharia under the title of good life, and marriage is regarded as a moral thing that strengthens the society; This path is from the side of ethics towards society, not that it is considered moral because it is a social matter. With this definition, the reason that has been raised about the immorality of marriage loses its color. In the end, it will be shown that marriage through rights and the emergence of mahram legal chains, the sanctity of marriage, inheritance and genealogy, strengthens the society.